2015
DOI: 10.15680/ijirset.2015.0401037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Powder Composition & Morphology on Green Density for Powder Metallurgy Processes

Abstract: Powder Metallurgy (PM) deals with products and processes which use raw material in the form of powders that are compacted into the required shape and size using suitable moulds. These compacted powders are called "Green Compacts". The properties of the component produced by PM processes are influenced by powder characteristics such as composition, morphology, particle size, distribution, and method of compaction. The first step in PM process is preparation of "green" compacts. Uni-axial pressing is one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Namun, serbuk baja dengan ukuran -31 µm lebih rentan terhadap pembentukan cacat selama tahap debinding dan sintering. [14]- [17] Kecacatan produk berkurang dengan meningkatkan laju pemanasan dan dengan meningkatkan gas laju aliran. Meskipun banyak penelitian telah dilakukan untuk mengevaluasi teknik paduan dan feedstock yang berbeda, namun sifat mekanik selain densitas produk sangat jarang diukur.…”
Section: Pendahuluanunclassified
“…Namun, serbuk baja dengan ukuran -31 µm lebih rentan terhadap pembentukan cacat selama tahap debinding dan sintering. [14]- [17] Kecacatan produk berkurang dengan meningkatkan laju pemanasan dan dengan meningkatkan gas laju aliran. Meskipun banyak penelitian telah dilakukan untuk mengevaluasi teknik paduan dan feedstock yang berbeda, namun sifat mekanik selain densitas produk sangat jarang diukur.…”
Section: Pendahuluanunclassified
“…Other factors determining the sealing of green compacts are the shape and size of the starting particles [11], the degree of wear of the press tool matrix, the temperature of the pressing process, etc. [12].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Suresh et al [17] have reported that the iron powders with an average particle size in the range of 2 to 150 microns show a linear relationship between green density and pressure. Daud et al [18] have reported that the grains and bulk density increase with increasing sintering temperature and sintering times.…”
Section: Powder Metallurgy Super Hexagonmentioning
confidence: 99%